2013
DOI: 10.2466/15.pms.117x19z4
|View full text |Cite
|
Sign up to set email alerts
|

Hardiness in Professional Spanish Firefighters

Abstract: As a high risk, physically demanding, and stressful profession, firefighting presents an ideal context for the study of hardiness. Hardiness of professional Spanish firefighters was assessed. Participants (53 firefighters; M age = 36.1 yr., SD = 8.2) volunteered to complete the adapted Spanish version of the Personal Views Survey. Results showed that participants' mean Hardiness score was slightly high. Hardiness was influenced by years of service. Spanish firefighters present a homogenous set of personal char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In the context of studies of firefighters, it is worth highlighting Chen-Lin's recent work (2014), which concludes that flow state has a positive influence on work satisfaction in volunteer firefighters. However, studies about this topic have not been performed in professional firefighters (De la Vega, Ruiz, Gómez, & Rivera, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of studies of firefighters, it is worth highlighting Chen-Lin's recent work (2014), which concludes that flow state has a positive influence on work satisfaction in volunteer firefighters. However, studies about this topic have not been performed in professional firefighters (De la Vega, Ruiz, Gómez, & Rivera, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is also recommended that resilience training be implemented to pre-empt potentially negative reactions of exposure to traumatic events, which may increase resilient responses following potentially traumatic circumstances (Pietrantoni and Prati, 2008; de la Vega et al , 2013). This echoes Sheehan et al 's (2004) recommendation for specialized pre-crisis education focussing on critical incident stress management.…”
Section: Discussionmentioning
confidence: 99%
“…They may be exposed to mass casualty incidents or firefighter death (SOP Center, 2010), leading to strong emotional reactions (Paton et al , 2000). Whilst emergency responders often demonstrate the ability to deal with said challenges (Shakespeare-Finch, 2011; de la Vega et al , 2013), continued exposure risks effective functioning (Rutkow et al , 2011) and development of mental health problems (Pietrantoni and Prati, 2008; Lee et al , 2014; Bobko; Kamin, 2015), including post-traumatic stress disorder (PTSD; Marmar et al , 1999; Laposa et al , 2003). Indeed, sickness-absence records show mental illness to be a common cause of firefighter absence (Governance, Audit and Scrutiny Committee, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Several of the selected studies found that firefighters are able to rely on personal and social resources to effectively cope with adversity, revealing high levels of resilience despite the frequent exposure to PTE (Blaney and Brunsden, 2015;Crowe et al, 2017;De la Vega and Ruiz, 2013;Meyer et al, 2012;Pietrantoni and Prati, 2008). Moreover, resilience seems to buffer against PTSD (Kim et al, 2018;Lee et al, 2014;Meyer et al, 2012;Onyedire et al, 2017;Shepherd et al, 2017), depression and anxiety (Khadem et al, 2017;Meyer et al, 2012;Straud et al, 2018) and burnout (Kaplan et al, 2017).…”
Section: Summary Of the Findingsmentioning
confidence: 99%